2007
DOI: 10.1055/s-0037-1617162
|View full text |Cite
|
Sign up to set email alerts
|

Langzeitprophylaxe bei kongenitaler Hämophilie mit Hemmkörpern

Abstract: A major challenge in the treatment of haemophilia patients is the development of autoantibodies against factor VIII. These patients are at particular risk if spontaneous bleedings or traumata occur or if surgery is necessary. In case of an unsuccessful immune tolerance therapy with high i.v. doses of factor VIII, treatment with recombinant factor VIIa or activated prothrombin complex should be considered. This article summarises data of three patients with severe haemophila A due to an inversion of intron 22 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…It was demonstrated that aPCC and rFVIIa are equally effective for the treatment of acute bleeds [49]. Some evidence points out that bypassing agents can also prevent significant percentage of bleedings and would thus justify a prophylaxis regimen with bypassing agent in selected severe cases of high-titre inhibitors [49,50,51,52]. Recently, some new strategies have been demonstrated to be capable of inducing hemostasis in patients with FVIII inhibitors: FVIII mimetic therapy [53], rebalancing hemostasis by anti-thrombin inhibition [54] and inhibition of tissue factor pathway inhibitor [55].…”
Section: Inhibitorsmentioning
confidence: 99%
“…It was demonstrated that aPCC and rFVIIa are equally effective for the treatment of acute bleeds [49]. Some evidence points out that bypassing agents can also prevent significant percentage of bleedings and would thus justify a prophylaxis regimen with bypassing agent in selected severe cases of high-titre inhibitors [49,50,51,52]. Recently, some new strategies have been demonstrated to be capable of inducing hemostasis in patients with FVIII inhibitors: FVIII mimetic therapy [53], rebalancing hemostasis by anti-thrombin inhibition [54] and inhibition of tissue factor pathway inhibitor [55].…”
Section: Inhibitorsmentioning
confidence: 99%
“…Die Häufigkeit dieser Erkran− kung liegt bei ca. 1 : 5000 der männlichen Neugebore− nen [1]. Die angeborene Hämophilie B ist um den …”
Section: Epidemiologie Und Genetikunclassified